ABOUT ‘ACADEMIC CAPITALISM’ AND ‘ENTREPRENEURSHIP UNIVERSITY’ - Alena I. Nefedova (Высшее образование в России, 2016)
In this paper, we reconsider concepts of ‘academic capitalism’ and ‘entrepreneurship university’, which are intensively discussed in higher education researches as a result of growing competition between universities from all over the world. Despite the fact, that the main books on this theme have been published nearly 20 years ago, their actuality is growing, especially in Russian context. We analyze the possible theoretical input of these concepts as well as possible empirical implications for the future research. The themes of ‘academic managerialism’ and ‘university as a corporation’ are also discussed.